The Effect of Performance Management on Performance with Employee Attitudes as Intervening at PT. Tissan Nugraha Globalindo - Sinarwati Sunarjo; Isalman Isalman; Asrip Putera (AIBPM Publisher, 2019)
The purpose of this study was to determine and analyze the effect of performance management on performance, the effect of performance management on employee attitudes, the effect of employee attitudes on employee performance and the influence of performance management on employee performance through employee attitudes as intervening variables. This research was conducted at PT. Tissan Nugraha Globalindo. The population and sample in this study amounted to 60 employees using the census method as a method of sampling. The analytical tool used for testing is Path Analysis. The results showed that performance management positively and significantly affected employee attitudes. Employee attitudes positively and significantly affect employee performance. Performance management positively and significantly influences employee performance. The attitude of employees does not mediate the relationship between performance management and the performance of employees of PT. Tissan Nugraha Globalindo. The results of this study contribute to practitioners in order to improve the performance of employees through improving performance management and employee attitudes.